An empirical examination of the effect of entrepreneurs biological makeup on the firm performance - Minai, Mohd Sobri; Lucky, Esuh Ossai Igwe; Abdul Rahman, Hamzah (Medwell Publishing, 2013)
In an attempt to investigate how entrepreneurs biological makeup contributes to the firm performance, a cross sectional study of questionnaire survey research design was conducted and data was generated from 182 entrepreneurs of small firms in both manufacturing and service industries in Lagos, Nigeria. The questionnaires were distributed through drop-off and pick up procedure of data collection. Overall, the findings indicate that there is a significant relationship between entrepreneurs biological makeup and firm performance. However at the dimensional level, the results show that family background childhood experience, friend influence and relative influence were not significantly related to firm performance while it was indicated that entrepreneurs early business exposure significantly affect firm performance. Based on the findings, it is concluded that entrepreneurs biological makeup as well as early business exposure is important in achieving firm performance.It is hoped that the findings of h s study would be beneficial to researchers, entrepreneurs, business-owners as well as policy makers in government.